Marketing effectiveness and accountability in SMEs a multimethological approach - Smith, Trevor A. 1958- (Palgrave studies in marketing, organizations and society)
This book sheds light on marketing effectiveness and accountability marketing in small and medium-sized enterprises (SMEs). Using a multi-method investigation, it includes a knowledge inquiry of marketing knowledge and customer knowledge, a qualitative inquiry utilizing semi structured interviews and thematic data analysis, a quantitative analysis utilizing survey and structural equations modelling, and a case study that employs both narrative (storytelling) data analysis and an accountability audit with a techno marketing SME. SMEs generally face financial constraints that limit their ability to carry out the marketing function. Addressing this limitation, the author presents conceptual models based on the resource based view and the knowledge based view to show how marketing capabilities can lead to performance improvement in the SMEs. The lessons learnt provide guidance in the practice of marketing for small and medium firms to be more effective in their marketing investments and make wiser marketing decisions. This book will prove useful for both researchers and practitioners by extending knowledge on marketing performance management in the SMEs. Trevor A. Smith is Senior Lecturer in Marketing and Methodology at Mona School of Business and Management in the University of the West Indies, Jamaica. His research focuses on marketing and consumer psychology. -- Provided by Publisher.